Communication of non-governmental organizations in Latin American scientific journals: Bibliometric analysis in Scopus and Latindex - Quintana Pujalte, Leticia (InMediaciones de la Comunicación, 2021)
Scientific journals are an instrument for validation and dissemination of research, as well as an important tool for sharing the produced knowledge. This article highlights the publication of studies related to the organizational communication of one of the frequently marginalized actors: non-governmental organizations (NGOs). A bibliometric study of 34 scentific articles published in Latin American scientific journals indexed in the Scimago Journal Ranking (SJR) of Scopus and the Latindex catalogue that refer to the organizational communication of NGOs is carried out. The results tell that the theoretical contributions are heterogeneous, although the strategic communication approach shows a consolidation process. The most widely used methods are documentary review and case analysis, which suggests an interest in the construction of a singular and Latin American perspective on a topic that is still in an incipient stage.